Integrating Models of Suicidality in Canadian Suicidology: A narrative synthesis / Intégration des modèles de suicidalité en suicidologie Canadienne : une synthèse narrative - Gay, Matias (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
Background: Suicide remains a critical public health issue requiring approaches that move beyond staticmodels. Traditional frameworks often operate in isolation, limiting their relevance in high-intensity settings,such as emergency departments (EDs). There is a growing need for integrative models that reflect the fluid and complex nature of suicidality in acute care.Objective: This narrative synthesis explores how diverse theoretical models can inform emergency nursing practice by framing suicidality as a dynamic and evolving process. The aim is to improve suicide risk assessment through an integrated, clinically relevant approach.Methods: A narrative synthesis was conducted to examine empirical and conceptual models with demonstrated relevance to emergency mental health. Frameworks included the Suicidal Careers Model, Narrative-Crisis Model, attachment theory, developmental perspectives, gender-based frameworks, and Suicide Crisis Syndrome (SCS). These models were selected for their predictive value, clinical utility, and explanatory power.Results: Suicidality emerges through the interaction of long-term vulnerabilities and acute crisis states. The integrated framework highlights the roles of insecure attachment, identity disruption, gender-based risk factors, and developmental stage. Special focus is placed on the experiences of gender-diverse individuals, who often fall outside traditional risk models.Conclusion: A multidimensional, developmentally attuned framework enhances suicide risk detectionand intervention in emergency settings. By accounting for identity, relational context, and crisis dynamics, this approach supports more inclusive and effective prevention strategies in frontline care.